DNA structural properties of DNA binding sites for 21 transcription factors in the mycobacterial genome - Dey, Upalabdha; Olymon, Kaushika; Banik, Anikesh; Abbas, Eshan; Yella, Venkata Rajesh; Kumar, Aditya (Frontiers in Cellular and Infection Microbiology, 2023)
Mycobacterium tuberculosis, the causative agent of tuberculosis, has evolved over time into a multidrug resistance strain that poses a serious global pandemic health threat. The ability to survive and remain dormant within the host macrophage relies on multiple transcription factors contributing to virulence. To date, very limited structural insights from crystallographic and NMR studies are available for TFs and TF–DNA binding events. Understanding the role of DNA structure in TF binding is critical to deciphering MTB pathogenicity and has yet to be resolved at the genome scale. In this work, we analyzed the compositional and conformational preference of 21 mycobacterial TFs, evident at their DNA binding sites, in local and global scales. Results suggest that most TFs prefer binding to genomic regions characterized by unique DNA structural signatures, namely, high electrostatic potential, narrow minor grooves, high propeller twist, helical twist, intrinsic curvature, and DNA rigidity compared to the flanking sequences. Additionally, preference for specific trinucleotide motifs, with clear periodic signals of tetranucleotide motifs, are observed in the vicinity of the TF–DNA interactions. Altogether, our study reports nuanced DNA shape and structural preferences of 21 TFs.